Production, characterization and acceptability of pineapple liqueurs prepared with different alcoholic bases - Oliveira, Érica Resende; de Deus, Kátia Oliveira; Caliari, Márcio (Revista Verde de Agroecologia e Desenvolvimento Sustentável, 2015)
Evaluation of physico-chemical parameters and the acceptability of liquors pineapple (Ananas comosus L. Merri), produced with different alcoholic bases: rum, flavored with pineapple peel and rum doubly distilled grain alcohol, were performed in this study. We conducted analyzes of alcoholic strength, density, pH, soluble solids, total fixed and volatile acidity, dry, and sensory analysis through the affective test of acceptability with 100 judges using 9-point hedonic scale to evaluate the attributes color, flavor , odor and overall impression, and purchase intent test. The average alcohol content found for all treatments was 25% v / v, a value that lies within the limits of the Brazilian law. The values of dry matter, fixed acidity, density and L * is not distinguished between treatments. The color parameters L *, a *, b *, chroma and H °, and the results of the analysis of the total acidity, soluble solid showed up only statistically different for liquor-based grain alcohol. The average pH differed for rum-based liqueur. All liquors showed good acceptability, averaging above 6 and 49% of the panelists claimed that the product would probably buy pineapple liqueur made with different alcoholic bases. The liquor made of only rum was the most accepted as the global average of items analyzed.